If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (c + d) * 2 = 0 Reorder the terms for easier multiplication: 2(c + d) = 0 (c * 2 + d * 2) = 0 (2c + 2d) = 0 Solving 2c + 2d = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2d' to each side of the equation. 2c + 2d + -2d = 0 + -2d Combine like terms: 2d + -2d = 0 2c + 0 = 0 + -2d 2c = 0 + -2d Remove the zero: 2c = -2d Divide each side by '2'. c = -1d Simplifying c = -1d
| 180n-360=162n | | 4y*4y=64 | | 4x-9=2+15 | | 9(x-2)+10x+10-20= | | 3=25x+6 | | 0=60x-16x^2 | | 5a+b+90=180 | | ln(3t)-ln(4t)=2 | | 4a-1=16.5 | | [3x+5]+4=13 | | 4=7m | | a(2a-1)(2a)=16.5 | | 80=-2(m+5)+m | | 8(1-8)=x+8 | | Cot^2(x)-cos(x)=1 | | 2a-1-a-2a=16.5 | | 180=5x-14+3x | | Cot^2x-cos(x)=1 | | 3(2x+10)-40+x+2x+10=162 | | (5+5i)(3-3i)=0 | | x^9=205 | | (100x^2-27)=0 | | -13=-22-3x | | 5a-1=16.5 | | 32-5[4+3(2+1)-6]= | | 9y-3=19-y | | y=50+2.5x | | 2x+10+x+3(2x+10)-40=162 | | 7+16x-1-4x=24+8x-9+3x | | X-6.4=-2.6 | | 72+(a+b)=180 | | 3m^2-11m-6=0 |